Reducing Force Ripples and Enhancing Reliability in LSRMs Through Modern Structure and Advanced Control Systems - Siamak Masoudi (21839609) (2024)
Linear switched reluctance motors (LSRMs) are highly popular due to their simple and robust structure, affordable pricing, and ability to operate at high efficiency. However, a major drawback of these motors is the high ripple force. In this paper, a novel structure for a linear motor with an exceptionally lightweight rotor and a stator with separate poles is presented, making it suitable for use in electric train systems. The proposed system not only significantly reduces force fluctuations but also enables the distribution of force along the length of the moving vehicle, ensuring smooth motion. Moreover, the reliability of the system is enhanced, as the LSRM can continue its motion even in the presence of a fault in one of the phases. In applications with high speeds, the use of a fast controller seems essential, but conventional fast regulators often lack sufficient precision. To address this issue, a new control system is introduced, utilizing a new 12-vector voltage switching table and a current controller. Unlike conventional control methods, the phases firing angle in the proposed system is not fixed. As a result, acceptable performance at different speeds is achieved through an adaptive real-time turn-on position control. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2024.3385437